TEACHER PERCEPTIONS ON THE USE OF QUIPPER SCHOOL APPLICATION IN TEACHING READING - Shasha Gunawan; Dian Erlina; Eko Saputra (Journal of Research on Language Education, 2023)
This study was focus on the teacher perceptions on the use of quipper school in teaching English reading. The study was conducted at SMA N 1 Kayu Agung. There were two English teachers who became the sample for this study. The aim of this study was to answer this following question; How were the teachers perceptions using quipper school application in teaching reading at SMA N 1 Kayuagung? A qualitative study was used for this study. Based on the result of this study, the English teacher assumed that Quipper School application is very helpful for teaching English reading. However, the researcher hope that the next study can conduct a deepen study on the students’ perception in leaning English reading using Quipper school.